The frequency dependence of hygro-expansive scaling of oak. Issue 1 (2nd January 2020) - Arends, T.; Pel, L.; Smeulders, D. M. J.
ABSTRACT: Fluctuations in the ambient relative humidity are often cyclic of nature, composed of a wide variety of frequencies. Variations may be as fast as one minute or as slow as a complete season. A wooden object exposed to these fluctuations exchanges moisture with the air, resulting in a change in the local moisture content of the wood. Since moisture penetration is affected by the timescale of the changes in ambient conditions, so are processes caused by moisture content variations. Moisture content variations cause dimensional changes of a wooden object, which, if mechanically restrained, lead to a buildup of stresses and ultimately to damage. It is therefore important to predict the frequency behavior of moisture content and expansion in wood. In the presented study, experiments are conducted in which the moisture content and expansion of oak cubes with different sizes is measured during sinusoidal relative humidity fluctuations with different frequencies. The amplitude in moisture content and expansion is shown to be simply scalable based on sample size only. Derived diffusion coefficients are in agreement with literature values, although the experimental frequency behavior is shown to deviate qualitatively from diffusive frequency behavior.